Ekonomi Indonesia Tahun 1950-an dan Penguasaan Negara terhadap Perusahaan Kereta Api Pasca KMB 1949 - Waskito Widi Wardodjo (Indonesian Historical Studies, 2018)
The prominent feature of the Indonesian economy in the 1950s was the dualistic nature that shows a division between the modern and subsistence traditional agriculture sector. The modern economy sector was the major industry controlled by Dutch companies. The focus of this research is to briefly describe the government's economic program as a new sovereign state such as the Benteng program. There are some major research problems which should be analyzed; (1) The Indonesian government's economic nationalization strategy to change the economic structure that is still controlled by the colonial; (2) The state's effort to nationalize Dutch companies, especially railway companies. There were eleven railway companies that were affected by the nationalization policy. The results show that both state-owned and private-owned railway companies were affected by nationalization eventually accepted the policy as a consequence of a sovereign state with certain compensation. It happened after going through quite a dynamic diplomacy.